The Multimodal Analysis of Lazada’s Online Advertisement - Br. Perangin-angin, Alemina; Nasution, Ely Hayati; Jalil, Zurriyati A. (TALENTA, 2022)
Advertisement plays an important role in the progression and development of a public company or an individual agency. The performance of an advertisement cannot be separated from the elements inside. The purpose of this research was to determine the relationship between image (visual elements) and text (linguistic elements) in a context. This research analyzed the multimodal aspect of Lazada's online advertisement. The data was obtained from the internet by accessing the legal website of Lazada and selecting one image as the sample. The method used in the research was a qualitative method that focused on descriptive and interpretative analysis. Generic Structure Potential (GSP) proposed by Cheong (2004) was applied to reveal visual and linguistic elements. Meanwhile, Halliday’s transitivity was applied to analyze types of processes in order to show how those elements represented the message conveyed. The research results showed that the visual elements on Lazada online advertisement were Lead, Emblem, and Display. Meanwhile, the linguistic elements were Announcement, Emblem, Call-and-visit-information, Enhancer, and Tag. Moreover, both elements were interconnected, in which attractive visual and linguistic elements directly affect the quality of the advertisement performed.